OPTIMIZING WORKFORCE DYNAMICS: A COMPARATIVE ANALYSIS OF REGIONAL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This annotation provides an overview of the key components of a comprehensive study on optimizing workforce dynamics through a comparative analysis of regional labor exchanges globally. The focus is on understanding the various models, policies, and technological innovations employed in different regions to enhance the efficiency and effectiveness of labor markets.